Variabilidade genética de populações de seleção recorrente de arroz, influenciada por macho‑esterilidade ou recombinação manual - Pinheiro, Letícia da Silveira; Rangel, Paulo Hideo Nakano; Vianello, Rosana Pereira; Brondani, Claudio (Pesquisa Agropecuaria Brasileira, 2012)
<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The objective of this work was to determine the effect of male sterility or manual recombination on genetic variability of rice recurrent selection populations. The populations CNA<span style="color: black; line-height: 115%; font-family: "MS Mincho"; font-size: 10pt; mso-bidi-font-family: "MS Mincho"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">‑<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IRAT 4, with a gene for male sterility, and CNA 12, which was manually recombined, were evaluated. Genetic variability among selection cycles was estimated using14 simple sequence repeat (SSR) markers. A total of 926 plants were analyzed, including ten genitors and 180 individuals from each of the evaluated cycles (1, 2 and 5) of the population CNA<span style="color: black; line-height: 115%; font-family: "MS Mincho"; font-size: 10pt; mso-bidi-font-family: "MS Mincho"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">‑<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IRAT 4, and 16 genitors and 180 individuals from each of the cycles (1 and 2) of CNA 12. The analysis allowed of the identification of alleles not present among the genitors for both populations, in all cycles, especially for the CNA<span style="color: black; line-height: 115%; font-family: "MS Mincho"; font-size: 10pt; mso-bidi-font-family: "MS Mincho"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">‑<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IRAT 4 population. These alleles resulted from unwanted fertilization with genotypes that were not originally part of the populations. The parameters of Wright’s F<span style="color: black; line-height: 115%; font-family: "MS Mincho"; font-size: 10pt; mso-bidi-font-family: "MS Mincho"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">‑<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">statistic (F<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 6pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IS <span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">and F<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 6pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IT<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">) indicated that the manual recombination expands the genetic variability of the CNA 12 population, whereas male sterility reduces the one of CNA<span style="color: black; line-height: 115%; font-family: "MS Mincho"; font-size: 10pt; mso-bidi-font-family: "MS Mincho"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">‑<span style="color: black; line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IRAT 4.